Optimal timing for faecal tagging in same day CT colonography for patients with failed colonoscopy. Issue 2 (May 2017) - Saluja, Sushant; Gaikstas, Grazvydas; Sapundzieski, Milan
Abstract: Aim: Same day CT colonography (CTC) for incomplete colonoscopy should be considered to avoid the need for further bowel preparation. Oral administration of contrast is essential for optimal colonic analysis of the CTC. Our aim was to determine the optimal time for giving contrast to people who underwent same day CTC after failed colonoscopy. Methods: Data was extracted from the Trust database to identify the number of CTC referrals following failed or incomplete colonoscopy within the last 5 years, and the reason for their referral. Patients were then excluded if they had not received faecal tagging, which included all patients prior to 2013. Two experienced radiologists independently reviewed the CTCs to determine the level of faecal tagging, and this was correlated with the estimated length of time between the administration of the contrast agent and the CTC examination. Results: 110 patients were identified within the 5 year period who had undergone same day CTC following failed colonoscopy. Reasons for the referral included incomplete colonoscopy (most common indication), contraindication to colonoscopy, poor colonoscopic view, refusal for colonoscopy and data unavailable. 60 patients had received faecal tagging, and two experienced radiologists independently reviewed these CTCs to determine the level of faecal tagging from the caecum to the rectum (complete bowel coverage). Conclusion: Our study suggests that contrast should be given approximately 256.4 ± 24.4 (4.27 h) minutes before same day CTC, but this time could be reduced where the left side of the colon had been successfully evaluated by colonoscopy. Further studies with multicentre collaborations are required. Highlights: Optimal timing for contrast administration prior to same day CTC is proposed. Contrast should be given approximately 256.4 ± 24.4 (4.27 h) minutes before same day CTC. Further studies with multicentre collaborations are required.